STRATEGI PENGEMBANGAN MANAJEMEN JEMBER FASHION CARNAVAL - Violeta Wosi Permata (Pascasarjana Institut Seni Indonesia Padang Panjang, 2018)
ABSTRACT Jember Fashion Carnival (JFC) is an annual event in the art event of fashion carnival that’s first time held in 2001. In this relatively long journey, JFC experienced several obstacles and one of them was that JFC would be stopped by Jember district government in 2009 because it’s not included in the list of the activity of Jember district government. The objective of this research is to analyze and formulate the management strategy of the Jember Fashion Carnival. The research method used was the descriptive qualitative method by using the approach of SWOT analysis. The result of this research is the position of SWOT analysis quadrant; the position obtained is in the position of quadrant I namely expansion (supporting offensive strategy) so it’s needed the selection of strategy by using strength and utilizing opportunity. The strategy that should be applied is to form cultural cooperation with other countries, to develop and increase the quality of organizational management, and to implement the international standardization of carnival such as the existence of the technological system to support the tradition of JFC event. Keywords: JFC, management, SWOT analysis, and strategy management ABSTRAK Jember Fashion Carnaval adalah sebuah event tahunan dalam ajang seni karnaval tata busana pertama kali terselenggara pada tahun 2001. Dalam perjalanan yang relatif panjang; bukan berarti JFC tidak memiliki kendala dalam penyelenggaraannya. JFC sempat akan diberhentikan oleh Pemerintah Kabupaten Jember pada tahun 2009, sebab bukan termasuk dalam daftar kegiatan Pemerintah Kabupaten Jember. Tujuan dari penelitian ini adalah untuk menganalisis dan memformulasikan strategi pengelolaan Jember Fashion Carnaval. Metode penelitian yang digunakan adalah metode kualitatif deskriptif, dengan menggunakan pendekatan analisis SWOT. Hasil dari penelitian ini adalah posisi dari kuadran analisis SWOT, posisi yang didapatkan berada pada posisi kuadran I yaitu ekspansion (mendukung strategi onfensif), sehingga diperlukan pemilihan strategi menggunakan kekuatan dan memanfaatkan peluang. Strategi yang sebaiknya diterapkan adalah membentuk kerjasama dalam bentuk kerjasama budaya dengan negara lain, pengembangan dan peningkatan kualitas manajemen organisasi, dan mengimplementasi standardisasi karnaval bertaraf internasional, seperti adanya sistem tekhnologi untuk menunjang tradisi event JFC.